2017
DOI: 10.1039/c7cy01130j
|View full text |Cite
|
Sign up to set email alerts
|

Control of stereoselectivity of benzylic hydroxylation catalysed by wild-type cytochrome P450BM3 using decoy molecules

Abstract: The benzylic hydroxylation of non-native substrates was catalysed by cytochrome P450BM3, wherein “decoy molecules” controlled the stereoselectivity of the reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
0
24
0
8
Order By: Relevance
“…Crystallisation of the P450BM3 haem domain in complex with decoy molecules has proven challenging, with only a few successful examples having been reported by us . Recently, two powerful third‐generation decoy molecules, N ‐( S )‐ibuprofenoyl‐ l ‐phenylalanine (SIbuPhe) and N ‐enanthyl‐ l ‐prolyl‐ l ‐phenylalanine (C7ProPhe, Figure a,b), have been demonstrated to be particularly suited to the hydroxylation of benzene in vitro and in vivo in whole‐cell biotransformations .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallisation of the P450BM3 haem domain in complex with decoy molecules has proven challenging, with only a few successful examples having been reported by us . Recently, two powerful third‐generation decoy molecules, N ‐( S )‐ibuprofenoyl‐ l ‐phenylalanine (SIbuPhe) and N ‐enanthyl‐ l ‐prolyl‐ l ‐phenylalanine (C7ProPhe, Figure a,b), have been demonstrated to be particularly suited to the hydroxylation of benzene in vitro and in vivo in whole‐cell biotransformations .…”
Section: Resultsmentioning
confidence: 99%
“…Crystals of the P450BM3 haem domain containing C7ProPhe diffracted to a resolution of up to 1.41 Å. Both SIbuPhe (Figure a) and C7ProPhe (Figure b) bound in a similar fashion to previously reported structures of P450BM3 with substrates and decoy molecules, engaging in major hydrogen‐bonding interactions with the hydroxyl group of Tyr51 and the backbone amides of Gln73 and Ala74. The overall fold of the SIbuPhe‐ and C7ProPhe‐bound P450BM3 structures was quite similar with an RMSD of 0.5 Å and was also similar to the AbiATrp‐bound P450BM3 haem domain, with an RMSD between 0.5 Å and 0.7 Å (over the Cα of 3–455 amino acids of subunit A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to optimizing the structure of decoy molecules for modulating the activity and selectivity of wild‐type P450BM3, Bell and co‐workers demonstrated that the catalytic activity of the decoy system could be improved in combination with engineered P450s . For cyclohexane hydroxylation, a rate‐enhancing variant of P450BM3, KT2 (A191T/N239H/I259V/A276T/L353I), obtained from directed evolution, resulted in the product formation rates of 484 and 483 min −1 per P450 in combination with perfluorinated carboxylic acids PFC9 and PFC10, respectively.…”
Section: Decoy Molecule Strategymentioning
confidence: 99%
“…In addition to optimizing the structure of decoy molecules for modulating the activity and selectivity of wild-type P450BM3, [20,[25][26][27] Bell and co-workersd emonstrated that the catalytic activity of the decoys ystem could be improved in combination with engineered P450s. [28] For cyclohexane hydroxylation,arate-enhancing variant of P450BM3, KT2 (A191T/ N239H/I259V/A276T/L353I), obtained from directed evolution, resultedi nt he product formation rates of 484 and 483 min À1 per P450 in combination with perfluorinated carboxylic acids PFC9 and PFC10, respectively.T hese rates are 700-, seven-, and fourfold highert han wild-type P450BM3, the P450BM3 variant KT2, and the pair of wild-type P450BM3 with PFC9, respectively.F urther screening of cycloalkanes of different sizes (C5, C6, C8, C10) with combinationso fP 450BM3 variants and various decoy molecules indicated that the catalytic turnover rate of smaller substrates could be significantly improved.…”
Section: Decoy Molecule Strategymentioning
confidence: 99%
“…Zudem wurde festgestellt, dass Täuschmoleküle der dritten Generation die Hydroxylierung von Benzol zu Phenol stark verbessern . Des Weiteren kann die Stereoselektivität der benzylischen Hydroxylierung durch Anpassen der Struktur der Täuschmoleküle der dritten Generation gesteuert werden . Diese Ergebnisse zeigen deutlich, dass die Ausnutzung der Substratfehlerkennung das Potential für die Oxidation einer breiten Auswahl kleiner organischer Moleküle besitzt.…”
Section: Figureunclassified